Progress in Artificial Intelligence: 21st EPIA Conference on Artificial Intelligence, EPIA 2022, Lisbon, Portugal, August 31-September 2, 2022, Proceedings - Marreiros, Goreti; Martins, Bruno; Paiva, Ana; Ribeiro, Bernardete; Sardinha, Alberto (Lecture Notes in Computer Science. Lecture Notes in Artificial Intelligence, 2022)
This book constitutes the proceedings of the 21st EPIA Conference on Artificial Intelligence, EPIA 2022, which took place in Lisbon, Portugal, in August/September 2022. The 64 papers presented in this volume were carefully reviewed and selected from 85 submissions. They were organized in topical sections as follows: AI4IS - Artificial Intelligence for Industry and Societies; AIL - Artificial Intelligence and Law; AIM - Artificial Intelligence in Medicine; AIPES - Artificial Intelligence in Power and Energy Systems; AITS - Artificial Intelligence in Transportation Systems; AmIA - Ambient Intelligence and Affective Environments; GAI - General AI; IROBOT - Intelligent Robotics; KDBI - Knowledge Discovery and Business Intelligence; KRR - Knowledge Representation and Reasoning; MASTA - Multi-Agent Systems: Theory and Applications; TeMA - Text Mining and Applications.